2 Maccabees 10:1-8: Who Wrote It and Where Does It Belong? - Trotter, Jonathan R. (Journal of Biblical literature, 2017)
Many commentators agree on two points about the development of 2 Maccabees: (1) the letters in 1:1-2:18 were not written by the author of the rest of the history, and (2) the account of the rededication of the temple in 10:1-8 has been relocated or inserted into the text. In contrast to the positions of these scholars, the primary purpose of this article is to demonstrate that the author of 2 Maccabees deliberately composed 10:1-8 for its current position in the epitome. To this end, I will respond to the arguments against both the location of this passage and its composition by the author of the rest of 2 Maccabees, contentions that depend on finding evidence of narrative disruption, distinctive language and style, and conflicting content between 10:1-8 and its context. Finally, I will show how the account of the repossession and purification of the Jerusalem temple is essential in accomplishing one of the main goals of the history, namely, the explanation of the origin of Hanukkah, and is interconnected with the rest of the narrative with regard to its placement, language, style, and content.